Public health air pollution impacts of pathway options to meet the 2050 UK Climate Change Act target: a modelling study - Martin L Williams; Sean Beevers; Nutthida Kitwiroon; David Dajnak; Heather Walton; Melissa C Lott; Steve Pye; Daniela Fecht; Mireille B Toledano; Mike Holland (NIHR Journals Library, 2018)
Background: The UK's Climate Change Act 2008 (CCA; Great Britain. Climate Change Act 2008. Chapter 27. London: The Stationery Office; 2008) requires a reduction of 80% in carbon dioxide-equivalent emissions by 2050 on a 1990 base. This project quantified the impact of air pollution on health from four scenarios involving particulate matter of ≤ 2.5 µm (PM2.5), nitrogen dioxide (NO2) and ozone (O3). Two scenarios met the CCA target: one with limited nuclear power build (nuclear replacement option; NRPO) and one with no policy constraint on nuclear (low greenhouse gas). Another scenario envisaged no further climate actions beyond those already agreed ('baseline') and the fourth kept 2011 concentrations constant to 2050 ('2011'). Methods: The UK Integrated MARKAL-EFOM System (UKTM) energy system model was used to develop the scenarios and produce projections of fuel use; these were used to produce air pollutant emission inventories for Great Britain (GB) for each scenario. The inventories were then used to run the Community Multiscale Air Quality model 'air pollution model' to generate air pollutant concentration maps across GB, which then, combined with relationships between concentrations and health outcomes, were used to calculate the impact on health from the air pollution emitted in each scenario. This is a significant improvement on previous health impact studies of climate policies, which have relied on emissions changes. Inequalities in exposure in different socioeconomic groups were also calculated, as was the economic impact of the pollution emissions. Results: Concentrations of NO2 declined significantly because of a high degree of electrification of the GB road transport fleet, although the NRPO scenario shows large increases in oxides of nitrogen emissions from combined heat and power (CHP) sources. Concentrations of PM2.5 show a modest decrease by 2050, which would have been larger if it had not been for a significant increase in biomass (wood burning) use in the two CCA scenarios peaking in 2035. The metric quantifying long-term exposure to O3 is projected to decrease, while the important short-term O3 exposure metric increases. Large projected increases in future GB vehicle kilometres lead to increased non-exhaust PM2.5 and particulate matter of ≤ 10 µm emissions. The two scenarios which achieve the CCA target resulted in more life-years lost from long-term exposures to PM2.5 than in the baseline scenario. This is an opportunity lost and arises largely from the increase in biomass use, which is projected to peak in 2035. Reduced long-term exposures to NO2 lead to many more life-years saved in the 'CCA-compliant' scenarios, but the association used may overestimate the effects of NO2 itself. The more deprived populations are estimated currently to be exposed to higher concentrations than those less deprived, the contrast being largest for NO2. Despite reductions in concentrations in 2050, the most socioeconomically deprived are still exposed to higher concentrations than the less deprived. Limitations: Modelling of the atmosphere is always uncertain; we have shown the model to be acceptable through comparison with observations. The necessary complexity of the modelling system has meant that only a small number of scenarios were run. Conclusions: We have established a system which can be used to explore a wider range of climate policy scenarios, including more European and global scenarios as well as local measures. Future work could explore wood burning in more detail, in terms of the sectors in which it might be burned and the spatial distribution of this across the UK. Further analyses of options for CHP could also be explored. Non-exhaust emissions from road transport are an important source of particles and emission factors are uncertain. Further research on this area coupled with our modelling would be a valuable area of research. Funding: The National Institute for Health Research Public Health Research programme.